PENGENDALIAN HAMA TONGKOL JAGUNG (Helicoverpa armigera Hubner ) DAN PENGGEREK BATANG (Spodoptera frugiferda) DENGAN MENGGUNAKAN JAMUR ENTOMOPATOGEN PADA TANAMAN JAGUNG MANIS DI DESA BANJARAN DELISERDANG - wizni fadhillah; Rini Susanti; Aisar Novita; Lisdayani Lisdayani (JURNAL AGROTEKNOSAINS, 2021)
Corn is the second important food crop commodity after rice. Besides being used as food, corn is also used as animal feed. The low yield of maize is caused by many factors including physical factors (climate, soil and land types) and biological factors (varieties, pests, diseases and weeds), as well as socio-economic factors. The polyphagous nature of Helicoverpa armigera and the unavailability of varieties that are resistant to these pests have caused control practices to be carried out to date still depend on the use of insecticides. Biological control agents such as M. anisopliae, Beauveria bassiana, and Bacillus thuringiensis are the main control components. Utilization of biological agents has several advantages, especially selectivity, although it must be admitted that it is not as effective as insecticides with chemically active ingredients. The use of entomopotagen fungi is an environmentally friendly pest control and can be propagated by farmers. The aim of this study was to determine the effectiveness of environmentally friendly entomopathogenic fungi in controlling corn cob pests (Helicoverpa armigera) and corn stem borer (Spodoptera frugiferda) in Banjaran Deliserdang Village. The research method used is non-factorial RAK. From this study it was found that the intensity of S. frugiferda attack with the use of the entomopathogenic fungus B. bassiana showed the best effect with the intensity of S. frugiferda attack which was 9.28% while the H. armigera pest used B. bassiana with an attack intensity of 9.08%. The use of B. bassiana can reduce the attack of S. frugiferda pests on corn plantations.